Local resection for placenta accreta spectrum: a conservative uterus sparing technique for anterior placenta accreta - Uysal, Gülsüm; Tanrıdan Okçu, Nefise; Eskimez, Eda; Saygılı Yılmaz, Esra (The European Research Journal, 2019)
Objective: To evaluate and describe a surgical approach for uterine preservation and management of postpartum hemorrhage in placenta accreta spectrum (PAS). Methods: We analyzed the data of patients who were diagnosed with placenta previa companied with PAS prenatally and subsequently performed cesarean section with local resection technique to manage postpartum hemorrhage and uterine preservation at our tertiary care center between January 2016 and August 2017. The technique includes the local resection of placental invasion site and suturing the new uterine edges without internal iliac artery ligation. Results: The diagnosis of placenta accreta spectrum anterior in all 11 cases was confirmed intraoperatively. Only 1 case underwent hysterectomy in a second operation. Two of cases had bladder injury. The mean operative time was 99 ± 30 minutes. The mean received packed red blood cells was 2.3 ± 1.0 units. The mean length of postoperative hospital stay was 4.5 ± 1.4 days. There was no late complications regarding coagulopathy and infection. No maternal mortality was observed. Conclusion: Local resection is an effective, safe and fertility preserving approach in selected patients with PAS.